Surgical Neuromodulation of Tinnitus: A Review of Current Therapies and Future Applications. Issue 4 (17th July 2018) - Rammo, Richard; Ali, Rushna; Pabaney, Aqueel; Seidman, Michael; Schwalb, Jason
Abstract : Introduction: Tinnitus is the conscious perception of an auditory sensation in the absence of external stimulus. Proposed theories are based on neuroplastic changes that occur due to sensory deprivation. The authors review the relevant literature on functional imaging and neuromodulation of tinnitus and describe potential targets for deep brain stimulation (DBS). Materials and Methods: A MEDLINE keyword and Medical Subject Heading term literature search was performed using PubMed for tinnitus, neuromodulation, DBS, transcranial magnetic stimulation, epidural electrode stimulation, intradural electrode stimulation, functional imaging, and connectivity. Data from these reports were extracted and reviewed. Results: Multiple imaging studies are employed to understand the pathophysiology of tinnitus. Abnormal regions and altered connectivity implicated in tinnitus include auditory pathway and limbic structures. Neuromodulation attempts to correct this hyperexcitable state by disrupting these aberrant oscillations and returning activity to baseline. Applied treatment modalities include transcranial magnetic stimulation, epidural/intradural electrode stimulation, and DBS. More recently, modulation of autonomic pathways through vagus nerve stimulation and paired auditory sounds has demonstrated tinnitus improvement via plasticity changes. Conclusions: DBS shows much promise as a therapeutic option for tinnitus. Stimulation of the auditory pathway, particularly the medial geniculate body, could counteract thalamocortical dysrhythmias and reduce gamma activity implicated in the tinnitus percept. Stimulation of the limbic pathway could decrease attention to and perception of tinnitus. Additional studies, focusing on the involvement of thalamic and limbic structures in the pathophysiology of tinnitus, are needed to support the use of DBS.